2009
DOI: 10.1002/cjce.20169
|View full text |Cite
|
Sign up to set email alerts
|

Use of ultrasound in petroleum residue upgradation

Abstract: Conventional processes for the upgradation of residual feedstocks, viz., thermal cracking and catalytic cracking are carried out in the temperature range of 400-520 • C. Such high temperatures can in principle be substituted by acoustic cavitation. In the present work, two vacuum residues, namely, Arabian mix vacuum residue (AMVR) and Bombay high vacuum residue (BHVR) and one asphalt, viz., Haldia asphalt (HA) were subjected to acoustic cavitation for different reaction times from 15 min to 120 min at ambient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 11 publications
0
27
0
2
Order By: Relevance
“…They observed 11 and 27 % reduction in mass of asphaltene from two different samples after a specific time of ultrasonic irradiation of bitumen. Furthermore, Sawarkar et al [18] reported that the reduction in asphaltene content of bitumen after ultrasonic treatment was due to the conversion of refinery residues to lighter hydrocarbons in the boiling range of gasoil fractions. Furthermore, among all the mid to high-sonication frequencies tested at different power inputs, lower mass of asphaltene was extracted from bitumen in sonication frequency of 574 kHz with power input of 83.33 %.…”
Section: Resultsmentioning
confidence: 99%
“…They observed 11 and 27 % reduction in mass of asphaltene from two different samples after a specific time of ultrasonic irradiation of bitumen. Furthermore, Sawarkar et al [18] reported that the reduction in asphaltene content of bitumen after ultrasonic treatment was due to the conversion of refinery residues to lighter hydrocarbons in the boiling range of gasoil fractions. Furthermore, among all the mid to high-sonication frequencies tested at different power inputs, lower mass of asphaltene was extracted from bitumen in sonication frequency of 574 kHz with power input of 83.33 %.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for adding water in #5, and also #3, #4, and #6, is that water is identified as a hydrogen donor in heavy oil upgrading processes . Some researchers have used water to produce water/oil emulsions before applying HCUP . In addition, due to its low viscosity and low vapour pressure, which assist in the occurrence of cavitation, water is used as the liquid medium in most applications …”
Section: Resultsmentioning
confidence: 99%
“…There are some substances which could be used as a hydrogen donor for HCUP. Water, sodium borohydride, tetralin, citric acid, ammonia, methanol, ethanol, formic acid, hydrazine, methane, pentane, naphtha, light crudes, and hydrogen are mentioned in the literature . Non‐organic substances would make an emulsion when added to the process as a hydrogen donor making oil heavier and more viscous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, heating of a sonicated medium is a common phenomena during UST. Calorimetric efficiency of ultrasonic equipment (defined as energy dissipated as heat per power input) can vary from as low as 2% (Sawarkar et al, 2009) to as high as 53% (Semagina et al, 2000). For example, in the latter case 25 mL of water-ethanol solution was heated from 26 1C to 70 1C after only 7 min of UST (Semagina et al, 2000).…”
Section: Introductionmentioning
confidence: 99%